FINANCIAL FEASIBILITY STUDY OF ENVIRONMENTAL LABORATORY ESTABLISHMENT AT XYZ FOUNDATION - Putri Endru Subekti, Zahra
XYZ Foundation, a non-profit organization established in 2008 by a major heavy equipment distributor in Indonesia, aims to support corporate social responsibility programs. The foundation plans to establish an accredited environmental laboratory to address environmental concerns and generate additional revenue. The project costs IDR10 billion which is a significant amount for the foundation. The foundation wants to discover the feasibility of this project and its risk. To assess the project's financial feasibility and risks, the study uses primary data from interviews, as well as secondary data such as historical and benchmark data. The data analysis involves six stages. Pro forma financial statements are constructed based on assumptions, and Free Cash Flow to the Firm (FCFF) is calculated. The Weighted Average Cost of Capital (WACC) is also determined for the financial feasibility study. Capital budgeting techniques, including NPV, IRR, PI, payback period, and discounted payback period, are employed to evaluate the project's feasibility. If the project is deemed feasible, the next stage assesses its risks. Alternative strategies are proposed by modifying various variables if it is considered unfeasible.